Intravenous Iron Therapy Reverses Myocardial Iron Deficiency and Improves Functional Capacity in Non-Anemic Heart Failure: A Meta-Analysis of Randomized Controlled Trials - Siswanto; Rudy Afriant (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Iron deficiency is a profound metabolic comorbidity in chronic heart failure, driving deleterious consequences on patient prognosis and functional independence. Crucially, these detriments manifest entirely independently of circulating hemoglobin. While guidelines advocate for intravenous iron in symptomatic heart failure patients, the isolated efficacy and underlying mechanisms in the strictly non-anemic demographic remain subjects of clinical scrutiny. Methods: A systematic review and meta-analysis of randomized controlled trials was executed, adhering to PRISMA guidelines. We aggregated data from 10 trials (such as FAIR-HF, CONFIRM-HF, HEART-FID, FAIR-HF2). The primary endpoint was functional capacity improvement, evaluated via the Standardized Mean Difference of the Six-Minute Walk Test distance and Peak Oxygen Consumption. Secondary endpoints incorporated skeletal/myocardial energetics and heart failure hospitalizations. Data from non-anemic subgroups were extracted. Pooled effects were derived using a DerSimonian and Laird random-effects model, accompanied by sensitivity and safety analyses. Results: Ten trials encompassing 7,545 patients were included, isolating approximately 4,120 individuals within the non-anemic, iron-deficient sub-stratum. Intravenous iron significantly improved functional capacity in non-anemic patients compared to placebo (Standardized Mean Difference: 0.42, 95% Confidence Interval: 0.28 to 0.56, p < 0.001). Mechanistic data revealed significant reductions in phosphocreatine recovery half-times, objectively signifying restored mitochondrial oxidative phosphorylation. Furthermore, intravenous iron yielded a significant reduction in cumulative heart failure hospitalizations within this subgroup (Risk Ratio: 0.81, 95% Confidence Interval: 0.72 to 0.91, p = 0.003). Safety profiles indicated a slightly elevated risk of transient hypophosphatemia with specific formulations, though severe adverse events were comparable to placebo. Conclusion: Intravenous iron therapy successfully reverses the metabolic detriments of myocardial iron deficiency in heart failure patients devoid of anemia, translating into substantial enhancements in exercise capacity and attenuation of morbidity. Routine biochemical screening for iron deficiency should be universally prioritized regardless of baseline hemoglobin.